Tamaddun: The View of Syed Muhammad Naquib Al-Attas Towards a New Concept of Islamic Civilization - Nur Hadi Ihsan; Fadhillah Rachmawati; Wan Mohd Azam Mohd Amin (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2024)
This brief article aims to analyze Syed Muhammad Naquib al-Attas' thoughts on tamaddun using the philosophy of history as a theoretical framework. This research elucidates that tamaddun is a state of human social life that has reached a high level of morality (ādab) and culture for society. The critical elements of tamaddun are al-dīn, ādab, and al-'ilm, which accumulate in 'ilm, amal, and iḥsan. Al-Attas defines Islamic civilization as a civilization that arises amid the multifariousness of cultures of Muslim communities of the world as a result of the permeation of the fundamental elements of the religion of Islam, which those communities have begun to arise from inside themselves, and a manifestation of integration in multifariousness as well as of multifariousness in unity. Al-Attas wants to show that Islam has arranged the Malay-Indonesian Archipelago for the coming modern world as proof that the world has been Islamized.